1986
DOI: 10.1103/physrevb.34.8279
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport in calcium-based metallic glasses

Abstract: New measurements of the x-ray structure factor, electrical resistivity, and thermopower for Ca-AlGa metallic glasses are reported and compared with our previous measurements for Ca-Al glassy metals. Comparison of results from electronic-structure calculations for CaAl, Ca3A1, CaGa, and Ca3Ga alloys in a dose-packed crystalline structure with experiment indicates that the Ca d band may dominate the electron-transport properties of these glassy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…We note immediately that we see no unusual magnitude for S at any concentration for either liquid ternary alloy system; in particular, S ∼ = 0 for the alloy Ga 25 Al 25 Ca 50 , a concentration close to that for which the amorphous alloy showed an unusually large magnitude [4] (see figure 2). Moreover, we also note that while dS/dx has the same sign for the ternary liquid and the amorphous solid alloys, its magnitude for the liquid alloys is about an order of magnitude smaller.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We note immediately that we see no unusual magnitude for S at any concentration for either liquid ternary alloy system; in particular, S ∼ = 0 for the alloy Ga 25 Al 25 Ca 50 , a concentration close to that for which the amorphous alloy showed an unusually large magnitude [4] (see figure 2). Moreover, we also note that while dS/dx has the same sign for the ternary liquid and the amorphous solid alloys, its magnitude for the liquid alloys is about an order of magnitude smaller.…”
Section: Discussionsupporting
confidence: 60%
“…It has also been reported [4] that, for amorphous Ga 20 Al 20 Ca 60 (and, to a somewhat lesser extent for Ga 10 Al 30 Ca 60 ), the measured thermopower, S, is unusually large, having a magnitude of about 10 µV • C −1 ; this was hard to understand considering that the components are all simple non-transition metals. In the present study we look for an unusual magnitude for S in the liquid ternary alloy at nearly the same composition.…”
Section: Introduction and Theorymentioning
confidence: 99%
“…Al 100−x Ca x , on the other hand, fits the systematics found before. This is not surprising, as it is known that d-typical properties occur in Ca-containing systems [35,36], i.e., E F lies inside the d-band, making Ca TM-like, with the according consequences for the plasma resonance.…”
Section: Concentration Dependencementioning
confidence: 64%
“…Being stimulated by the first pioneering work by St Amand and Giessen [1], a number of Ca-based amorphous alloys have been synthesized and their atomic and electronic structures have been extensively studied in the past decade [2][3][4][5][6][7][8][9][10]. From the point of view of the electron transport properties, the amorphous Ca-M binary alloys have received particular attention because the resistivity is only about 50 µ cm for M = Mg, whereas it exceeds 400 µ cm for M = Al and Ga [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the electron transport properties, the amorphous Ca-M binary alloys have received particular attention because the resistivity is only about 50 µ cm for M = Mg, whereas it exceeds 400 µ cm for M = Al and Ga [3,4]. Naugle et al [5] revealed that the replacement of Al by Ga further increases the resistivity in the Ca-Al-Ga alloys. Mizutani et al [6] studied systematically the Al concentration dependence of the electrical resistivity and electronic specific heat coefficient in the amorphous Ca 70 Mg 30−x Al x and Ca 60 Mg 40−x Al x ternary alloys and discussed a sharp increase in resistivity with increasing Al concentration in terms of a decreasing density of states at the Fermi level.…”
Section: Introductionmentioning
confidence: 99%